Resposta a Agier, Bueno e Ullberg - Lins Ribeiro, Gustavo (Anuário Antropológico, 2023)
It is truly a privilege to receive comments from Michel Agier, Carmen Bueno and Susann Ullberg, colleagues whom I admire and who have been interlocutors in my own trajectory in different ways. I thank Anuário Antropológico for this opportunity to engage with them. I have tried to respond to their sophisticated observations as far as I could, but I am unsure whether I have succeeded. In any event, I express my gratitude to my three colleagues for their readings and thought-provoking comments: muito obrigado.